2021
DOI: 10.1021/acssuschemeng.1c01163
|View full text |Cite
|
Sign up to set email alerts
|

Fumaric Acid Assistant Band Structure Tunable Nitrogen Defective g-C3N4 Fabrication for Enhanced Photocatalytic Hydrogen Evolution

Abstract: Tuning the structural defects of graphite carbon nitride (g-C3N4) is an effective strategy to modify its band structure and promote charge separation, but it is still limited by complex and harsh preparation processes. Herein, g-C3N4 with nitrogen defects were fabricated by one-pot thermal polymerization of urea and fumaric acid. The N–(C)3 site, being the active site for photocatalytic hydrogen evolution, reached at a rate of 94.1 μmol·h–1, which was approximately 2.64 times that of the original g-C3N4. Nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 65 publications
(111 reference statements)
0
27
0
Order By: Relevance
“…As an intrinsic defect in a semiconductor crystal, vacancies can function as an electron trap to prevent the recombination of photogenerated electron–hole pairs or become a center for electron–hole recombination, which depends on the energy level of the vacancies. Previous reports have showed that the appropriate introduction of vacancies into photocatalytic materials including TiO 2 with O vacancies and g-C 3 N 4 with N or C vacancies could significantly improve the photocatalytic activities. Crystalline CdS exhibits n-type semiconductor characteristics because of its intrinsic S vacancies, while Cd 1– x Zn x S solid solution has been proven to be a stronger n-type semiconductor as compared to CdS . More recently, several studies have demonstrated that the presence of the surface defects such as S vacancies in the Cd 1– x Zn x S solid solution is beneficial for the photocatalytic H 2 evolution. , Nevertheless, the nature of physical chemistry for the role of the S vacancies in effectively capturing photogenerated electrons to promote the efficient separation of photogenerated electron–hole pairs is still less understood.…”
Section: Introductionmentioning
confidence: 99%
“…As an intrinsic defect in a semiconductor crystal, vacancies can function as an electron trap to prevent the recombination of photogenerated electron–hole pairs or become a center for electron–hole recombination, which depends on the energy level of the vacancies. Previous reports have showed that the appropriate introduction of vacancies into photocatalytic materials including TiO 2 with O vacancies and g-C 3 N 4 with N or C vacancies could significantly improve the photocatalytic activities. Crystalline CdS exhibits n-type semiconductor characteristics because of its intrinsic S vacancies, while Cd 1– x Zn x S solid solution has been proven to be a stronger n-type semiconductor as compared to CdS . More recently, several studies have demonstrated that the presence of the surface defects such as S vacancies in the Cd 1– x Zn x S solid solution is beneficial for the photocatalytic H 2 evolution. , Nevertheless, the nature of physical chemistry for the role of the S vacancies in effectively capturing photogenerated electrons to promote the efficient separation of photogenerated electron–hole pairs is still less understood.…”
Section: Introductionmentioning
confidence: 99%
“… 58 The introduced –OH group could increase the surface hydrophilicity of the fabricated TCN heterostructures, which is helpful for enhancing the photocatalytic activity of H 2 evolution. 47 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the above experimental results, we believe that the plasma modification strategy proposed in this paper can effectively control the defect structure and electronic structure of g-C3N4 material to promote its photocatalytic activity. Although the introduction of appropriate carboxyl groups is beneficial to the g-C3N4 polymer semiconductor, the preparation methods are limited long-term [10,38]. The non-thermal microwave Based on the above experimental results, we believe that the plasma modification strategy proposed in this paper can effectively control the defect structure and electronic structure of g-C 3 N 4 material to promote its photocatalytic activity.…”
Section: Visible-light-driven H 2 Evolution Performances and Optimiza...mentioning
confidence: 85%
“…The non-thermal microwave Based on the above experimental results, we believe that the plasma modification strategy proposed in this paper can effectively control the defect structure and electronic structure of g-C 3 N 4 material to promote its photocatalytic activity. Although the introduction of appropriate carboxyl groups is beneficial to the g-C 3 N 4 polymer semiconductor, the preparation methods are limited long-term [10,38]. The non-thermal microwave plasma method developed here is able to process samples at the kilogram level within minutes in the laboratory stage [39,40], and thus is promising in the rational design and low-cost, scaled-up preparation of structure precisely modulated materials for industrial application.…”
Section: Visible-light-driven H 2 Evolution Performances and Optimiza...mentioning
confidence: 99%